COVID like illness versus COVID-19 (CLIC STUDY) – Clinical profile and outcome - Jeetendra Kumar J Mood,; Rajanna, Avinash H; Vaibhav S Bellary,; Gowda, Gowtham S; Marimuthu, Yamini (Asian Journal of Medical Sciences, 2022)
Background: In December 2019, several cases of acute respiratory illness were detected in Wuhan city of China. This SARS-CoV-2 has been rapidly spreading worldwide ever since. SARS-CoV-2 has the potential to damage the vital organs such as lung, heart, liver, and kidney, and infection poses a considerable risk to patients by the high prevalence of pneumonia. Aims and Objectives: The objectives of the study are as follows: (1) To study clinical profile and biochemical markers in SARI patients. (2) To compare the clinical profile and biochemical markers between SARS-CoV-2 positive and negative patients and their outcomes. Materials and Methods: The present study is a hospital-based prospective cross-sectional study conducted on a total of 350 patients (150 SARI+200 COVID-19) in Bengaluru during the study period from June 2020 to May 2021. Results: Diabetes mellitus was present in 30% of SARI and 42% in COVID-19 patients (P=0.03). Leukocytosis (Total Leukocyte Count [TLC] >11000 cells/mm3) was more common among SARI patients than COVID-19 patients (49.3% vs. 24.3%). Leukopenia (TLC <4000 cells/mm3) was significantly more common in COVID-19 patients than in SARI patients (10.2% vs. 3.6%, P<0.001). Conclusion: COVID-19 infection is more common in patients with comorbidities such as diabetes mellitus and hypertension than SARI. Leukopenia was more common in COVID-19 patients whereas leukocytosis was more common in SARI patients.